2008
DOI: 10.1258/ijsa.2007.007149
|View full text |Cite
|
Sign up to set email alerts
|

Time to use text reminders in genitourinary medicine clinics

Abstract: Faced with a national 48-hour waiting time target and high non-attendance rates for booked appointments, our sexual health service sought patient preferences for appointment reminders. Questionnaires were distributed to 350 consecutive genitourinary medicine clinic attendees. Eighty-eight percent of respondents approved of appointment reminders, with text messaging being the preferred option. Automated voicemail reminders to mobile phones were acceptable to 84%. Patients would generally choose a voicemail remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…In an acquired immunodeficiency syndrome (AIDS) clinic serving young adult patients, a high percentage of whom were mobile phone users, SMS was the preferred option. 200 In a different study of adolescents attending dental clinics, participants reported a significant preference for letter reminders (56.3%), followed by telephone reminders (26.0%) and SMS reminders (17.7%). 55 Patient preferences for reminders appear to vary considerably, and we hypothesise that this may be related to sociodemographic factors such as age, employment status, etc.…”
Section: Simple Remindersmentioning
confidence: 97%
See 2 more Smart Citations
“…In an acquired immunodeficiency syndrome (AIDS) clinic serving young adult patients, a high percentage of whom were mobile phone users, SMS was the preferred option. 200 In a different study of adolescents attending dental clinics, participants reported a significant preference for letter reminders (56.3%), followed by telephone reminders (26.0%) and SMS reminders (17.7%). 55 Patient preferences for reminders appear to vary considerably, and we hypothesise that this may be related to sociodemographic factors such as age, employment status, etc.…”
Section: Simple Remindersmentioning
confidence: 97%
“…25 Numerous studies suggest that as many as 80-90% of patients have a positive attitude to receiving a reminder that jogs the memory. 55,79,145,200 The evidence presented indicates that the use of simple reminders is both acceptable and feasible across a wide array of health-care settings. Although very few studies have investigated the influence of preference on reminder effectiveness [see Chapter 4, Evidence statement (B.4): very few studies investigated whether or not the reminder preferences of the patient may influence the impact a reminder has on the patient's appointment behaviour (evidence category VIIa)], it may provide some indication about a patient's ability to access the reminder, which may ultimately influence the effectiveness of the reminder [see Chapter 4, Evidence statement (B.1): there is strong consistent evidence that the reminder may not be received by the patient (evidence category Ia)].…”
Section: Simple Remindersmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related text messaging via mobile phones started with routine appointment reminders. 17,18 Text messaging has subsequently been tested as a tool to engage patients with a variety of medical conditions. Motivational text messages to young children with type 1 diabetes mellitus have demonstrated positive effects on diabetes control and adherence.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recent studies indicate that patient preference for appointment reminders was via use of short message service (SMS) text messages over all other forms of communication. [5][6][7][8][9] Textmessage reminders have shown benefit in the clinical care of patients with asthma, 10 diabetes mellitus, 11,12 travelers vaccination, 13 smoking cessation, 14,15 and increasing compliance with oral contraceptives. 12 More recently, Armstrong et al 16 demonstrated that daily text-message reminders increased patient's adherence to daily sunscreen use by 26%.…”
mentioning
confidence: 99%